Art auctions spectacle and value in the 21st century - Brown, Kathryn (Lund Humphries, 2024)
This accessible new book offers a fresh view of art auctions, exploring their multifaceted role in today’s international art market and their transformation into spectacular theatres of the contemporary art world. From glittering black-tie events to the anonymity of the digital realm, auctions stage the creation of value and can make or break artists’ careers. They are a strange phenomenon: relics from the 18th century which remain at the heart of the art market. And yet art auctions have undergone huge change in the past decades, adapting to online formats, encroaching on territory which was once the preserve of galleries, and expanding ruthlessly into new regions and categories. Kathryn Brown's incisive new survey assesses the ongoing relevance of auctions to contemporary art markets and discusses the opportunities, controversies and conflicts of value to which they give rise
Keywords: Geschichte 2000-2024; Kunsthandel; Kunstauktion